Epigenetic Maintenance of Acquired Gene Expression Programs during Memory CD8 T Cell Homeostasis - Abdelsamed, Hossam A.; Zebley, Caitlin C.; Youngblood, Ben (Frontiers in Immunology, 2018)
Memory CD8 T cells have a unique ability to provide life-long immunity against pathogens containing their cognate epitope. Because of their ability to provide life-long protection, the generation of memory T cells is now a major focus for current vaccination or adoptive cell therapy approaches to treat chronic viral infections and cancer. It is now clear that maintenance of memory CD8 T cells occurs through a process of antigen-independent homeostatic proliferation, which is regulated in part by the gamma chain cytokines IL-7 and IL-15. Here, we will describe the role of these cytokines in the survival and self-renewal of memory CD8 T cells. Further, we will describe the role of epigenetics in the maintenance of acquired functions among memory CD8 T cells during homeostatic proliferation.